Ästhetik in der traditionellen Landschaftsgeographie und in der postmodernen Geographie - die Renaissance eines klassischen Paradigmas? - Gelinsky, Eva (ERDKUNDE, 2001)
In discussions of so-called postmodernism which have been taking place both within and without the academy, aesthetics, aesthetical experience and an ‚aestheticisation' of reality are frequently mentioned. Next to philosophy, the humanities in general, and the social sciences, (German-speaking) geography has taken these issues on board. Especially Hasse and Strassel engage with the problems of aesthetics from a postmodernist perspective. With their work, both authors initially assume an increasing significance of aesthetics. From a reality that is characterised as postmodern and aesthetisised Hasse and Strassel deduce the claim that geography as a discipline also has to engage with the boom of aesthetics. Here, traditional theories and methods could no longer capture the aesthetic design of, e.g., urban open spaces. Required were instead a tool for gaining knowledge about aesthetics which is well adapted to aesthetisised objects. This is what Strassel calls aesthetical knowing or in Hasse's words aesthetical thinking. Neither Hasse's nor Strassel's argument for an incorporation of aesthetical knowing or thinking refers directly to the classical landscape geography, although this tradition already attributed an important role to aesthetics in the processes of gaining knowledge. However, a fundamental correspondence between the here presented postmodern approaches and the traditional landscape paradigm can be found.